Gaschromatographic determination of phenol, methylphenols, chlorophenols, nitrophenols and nitroquinones in water at 0.1 μ g l−1 - Geißler, Andreas; Schöler, Heinz Friedrich (Water research, 1994)
A sensitive method for the analysis of phenol, 2 monomethylphenols, 8 chlorophenols and 7 nitrophenols in minor polluted waters at 0.1 and 0.25 μg l−1 concentration is reported involving continuous liquid-liquid extraction with a light phase rotary perforator, derivatisation either with diazomethane or with trimethylsulfonium hydroxide (TMSH) and analysis by GC-MS. Emphasis was laid on simple derivatisation procedures. The reaction yields with diazomethane in the presence of catalytical amounts of methanol were higher than 85% for all compounds except phenol, the methylphenols and nitrohydroquinone. TMSH gave high reaction yields for the chlorophenols only. The combination of rotary perforator extraction and diazomethane methylation ensured generally high recoveries from a drinking water matrix and may be carried out in routine work. Solid phase extraction with commercial RP-C18 cartridges (1 g, 11 water sample) with and without addition of 30 g l−1 sodium chloride to the sample yielded generally lower recoveries, especially for phenol, the methylphenols and some of the nitrophenols.
Elektronische Reproduktion der Druck-Ausgabe 10. April 2003
Gesehen am 09.02.2023
Im Titel ist -1 hochgestellt
Im Titel ist "my" als griechischer Buchstabe dargestellt